IMPLEMENTATION OF HIGH FIDELITY PROTOTYPING IN ONLINE FIELD PLACEMENT PROGRAM SYSTEM DESIGN - Gunadi, Goldie; Budiyantara, Agus (ISTEK WIDURI, 2021)
Service activities carried out by the Academic and Student Administration Bureau (BAAK) STMIK Widuri for students who will carry out field placement program (KKP) are currently still carried out conventionally, this makes the process of making KKP cover letters and also assignments for supervisors takes time, which is quite long and less efficient. To overcome these problems, it is necessary to create a web-based application system that can simplify and speed up the activities of student KKP administration services. In this study, observations were made on the current system modeled using Business Process Modeling Notation (BPMN) and Data Flow Diagrams (DFD). The problem analysis process uses the Root Cause Analysis (RCA) method. The system design runs with UML diagrams, namely Use Case, Activity and Deployment Diagrams. Making a prototype with a high fidelity concept using the PHP programming language, HTML 5, CSS, jQuery, Bootstrap and DataTables frameworks and the Chart.js library. This research resulted in a prototype that describes the overall functionality of the Online MPA system, interactive and has an attractive interface.